2021
DOI: 10.1155/2021/6634299
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Mechanism and Support Technology of Deep and High‐Stress Soft Rock Roadway

Abstract: In this study, the analysis and control of stability of surrounding rock in deep fractured soft rock roadway located in the underground mine of Jinfeng gold mine in Guizhou Province, China, has been investigated. The surrounding rock of roadway has been analyzed to characterize its deformation and failure mechanism through field survey, testing of rock physical and mechanical properties, in situ stress measure, analysis of mineral components of rock, and investigation of rock fragmentation degree. Based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Multiple periods of tectonic movement have occurred in the mine, resulting in complex geological circumstances for the ore body's occurrence. During the deep mining process, the surrounding rock of the deep roadway has encountered challenges such as large deformation and support difficulties [30,31].…”
Section: Application Prospect Analysis Of Damage Variable Based On Fr...mentioning
confidence: 99%
“…Multiple periods of tectonic movement have occurred in the mine, resulting in complex geological circumstances for the ore body's occurrence. During the deep mining process, the surrounding rock of the deep roadway has encountered challenges such as large deformation and support difficulties [30,31].…”
Section: Application Prospect Analysis Of Damage Variable Based On Fr...mentioning
confidence: 99%
“…Through indoor tests, numerical calculations, and field tests, Li (Li et al, 2015) analyzed the composition and microstructure of mudstone and obtained the hydration law of mudstone and its characteristics of strength weakening as well as the deformation and damage characteristics of surrounding rock under the action of the hydration. Zheng (Zheng et al, 2021) studied the effects of different factors on the stability of soft rock roadways based on numerical simulation techniques. It was found that high ground stress, rock fragmentation, and poor lithology are the factors that lead to the instability of the roadway; besides, physical and mechanical properties of the surrounding rock and the bearing capacity of the surrounding rock layer can be promoted to maintain the stability of the roadway with broken soft rock.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [12] put forward an innovative "relief-retaining" control technology of oor heave, which is a comprehensive measure that is composed of cutting groove in the oor, drilling for pressure relief at the roadway side, and setting retaining piles at the junction of roadway side and floor. Based on numerical simulation, Zheng et al [13] improved the bearing structure of support and proposed a high-strength combined support system with higher integrity and bearing capacity, which is consisted of cable bolt, fiber-reinforced shotcrete, steel mesh, split sets, resin bolt, and cement grouting. Wang et al [14] proposed a double-shell grouting technology with low-pressure grouting and high-pressure split grouting to improve the overall mechanical properties of the surrounding coal and rock mass and prevent the large deformation and failure of the roadway.…”
Section: Introductionmentioning
confidence: 99%